Influência das mudanças climáticas no cultivo da cana-de-açúcar no Estado da Paraíba - Silva, Wallysson Klebson de Medeiros (2019)
Climate change poses a major challenge for Brazilian agriculture, due to the dependence of crops on climatic elements such as precipitation, relative humidity, temperature and solar radiation. The objective of this work was to analyze the influence of climate changes on the cultivation of sugarcane in the state of Paraíba. For this, different datasets were used, namely: meteorological data of average temperature, total precipitation and relative humidity, obtained from the National Institute of Meteorology; data from temporary agricultural crops obtained from the Brazilian Institute of Geography and Statistics and the Institute of Applied Economic Research; data on the emission of greenhouse gases extracted from the Greenhouse Gas Emissions and Removal Estimate System; in addition to the databases of SimaPro® and through a field experiment carried out in the municipality of Pedras de Fogo, in the state of Paraíba. Calculations were performed using statistical methods (Mann-Kendall trend test and multiple linear regression technique), econometric (regression with panel data), economic (shift-share) and life-cycle assessment environmental impacts). The results showed that there were impacts of climatic variables on the production of sugarcane in the municipalities of Paraíba; the precipitation was a positively correlated conditioner and the temperature influenced negatively. Significant trends were also observed, mainly in relation to temperature, with a tendency to grow in the majority of the meteorological stations analyzed and to decrease to the relative humidity of the air. A heterogeneous response of impacts to the mesoregions was observed, with municipalities belonging to Mata Paraibana having a higher probability of producing sugarcane compared to other mesoregions. In the decomposition of Area Effects (EA), Yield (ER) and Geographic Location (ELG) a heterogeneous expansion was observed, with productivity gains explained by EA and ELG, since the ER showed the low agricultural dynamism. The decomposition of the area effect on scale and substitution effects of sugarcane and pineapple were the ones that absorbed the most areas, while the beans yielded more areas for the other crops. The application of multiple linear regression showed that the amount of sugarcane produced had a positive and significant correlation with the greenhouse gases (CO2 and N2O). According to the life cycle assessment study, the use of biosolids as fertilizer for sugarcane proved to be more environmentally viable, with higher productivity and lower emissions of produced carbon dioxide, reducing the carbon footprint and solving the problem of final destination of this waste.